Empirical Bayes Test for the Parameter of Rayleigh Distribution with Error of Measurement (Communications in Mathematical Research, 2021)
For the data with error of measurement in historical samples, the empirical Bayes test rule for the parameter of Rayleigh distribution is constructed, andthe asymptotically optimal property is obtained. It is shown that the convergencerate of the proposed EB test rule can be arbitrarily close to $O(n^{−\frac{1}{2}})$ under suitableconditions.
Keywords: error of measurement; empirical Bayes; asymptotic optimality; convergence rate.